Rhytidectomy Incision Techniques and Scar Outcomes: A Scoping Review - Liu, Katherine Y.; Chou, David W.; Verma, Hannah; Sehgal, Gavneet; Gregory, Jill K.; Gidumal, Sunder; Husain, Solomon; Kontis, Theda C.; Abraham, Manoj T. (Facial Plastic Surgery, 2024)
Although scar outcomes in rhytidectomy are crucial to patients and surgeons alike, there is a lack of consensus on incision techniques for optimizing rhytidectomy scars. A comprehensive scoping review of the literature was performed on rhytidectomy incision techniques and associated scar outcomes.The PRISMA protocol was utilized to conduct a scoping review of the literature through MEDLINE, EMBASE, and Science Citation Index databases to identify articles discussing rhytidectomy incision techniques and scar outcomes.A total of 49 studies were included in this scoping review. Four themes were identified related to rhytidectomy scars within these studies: temporal incision placement, tragal incision placement, lobule management, and postauricular incision design. Techniques within each theme were described and reported scar outcomes summarized.There are many approaches to rhytidectomy incisions described in the literature, with reportedly low rates of scar complications for each of the techniques described. It cannot be elucidated which techniques are superior due to the heterogeneity of outcomes reported in the literature with significant variability in outcome measures, study design, and follow-up time. Future studies should focus on utilizing a standardized rating system to aid in objective determination of the superiority of one technique versus another.Level of Evidence: Level I
Keywords: rhytidectomy; facelift; scar